Marketing strategy : a decision-focused approach - Walker, Orville C.; Mullins, John W. (John Walker) (Boston : McGraw-Hill Irwin, 2008)
This text covers the concepts and theories of creating and implementing a marketing strategy, and offers a focus on the strategic planning process and marketing's interfunctional relationship.
Includes bibliographical references and indexes.
Keywords: Marketing -- Management; Lehrbuch